Contrasting Some Differences in Managing Advanced Unresectable Hepatocellular Carcinoma Between the East and the West. Issue 8 (August 2019) - Lee, V.H.F.; Seong, J.; Yoon, S.M.; Wong, T.C.L.; Wang, B.; Zhang, J.L.; Chiang, C.L.; Ho, P.P.Y.; Dawson, L.A.
Abstract: Hepatocellular carcinoma (HCC) is a common malignancy worldwide, although its aetiologies vary significantly between the East and the West. About a half of HCC cases present with advanced unresectable HCC at the time of diagnosis, leading to a worse prognosis. Over the past 20 years, the treatment paradigm for advanced unresectable HCC has shifted from an entirely palliative approach to a multidisciplinary treatment, with continuous reassessment and possible repeat treatment attributed to the advent of novel and improved local, regional and systemic therapeutic options, contributed by both the East and the West. An individualised treatment plan should be determined for each patient, as there can be substantial differences in the decision-making and treatment response to the same treatment for different patients and different patient populations. This review provides a summary of the recent advances in management and compares Eastern and Western strategies for HCC.